1988
DOI: 10.1159/000199736
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Toxicity of Dietary <i>Phaseolus vulgaris</i> Lectins in the Rat: An Integrative Assay

Abstract: It is now generally admitted that phytohemagglutinin (PHA) constitutes the main factor responsible for the dietary toxicity of raw kidney beans. In the growing rat, an impairment of growth is the unique expression of a malnutrition syndrome. The aim of this work was to precise to what extent the intestinal injuries may account for this malnutrition. PHA was administered for 9 days to growing rats at levels ranging from 0.0025 to 0.25% of food dry matter. One group of controls was fed ad libitum and other group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…The sucrase activity in 3-week-old BBMV diminished significantly in the presence of Con A (T1) and when the lectin was pre-incubated with the enzyme (T3). Previous studies using Phaseolus vulgaris lectins have demonstrated that their specific interaction with membranes depends on the pattern of glycosylation of the mucosa (Begbie and King, 1985;Lafont et al, 1988), which can vary depending on diverse factors such as the age and diet composition (Sharma et al, 1997). These factors may partly explain the results obtained in the present work.…”
Section: Effects Of Con a On Digestive Enzyme Activitiessupporting
confidence: 56%
“…The sucrase activity in 3-week-old BBMV diminished significantly in the presence of Con A (T1) and when the lectin was pre-incubated with the enzyme (T3). Previous studies using Phaseolus vulgaris lectins have demonstrated that their specific interaction with membranes depends on the pattern of glycosylation of the mucosa (Begbie and King, 1985;Lafont et al, 1988), which can vary depending on diverse factors such as the age and diet composition (Sharma et al, 1997). These factors may partly explain the results obtained in the present work.…”
Section: Effects Of Con a On Digestive Enzyme Activitiessupporting
confidence: 56%
“…"Pinto" (94.7 g/100 g body weight) during 8 days was remarkably reduced compared to control (65.5 g/100 g body weight). In 1988, Lafont et al [15] administered purified PHA for 9 days to growing rats at levels ranging from 0.0025% to 0.25% of food dry matter. They noticed that PHA reduced the food intake when offered at a level higher than 0.04%.…”
Section: Discussionmentioning
confidence: 99%
“…25 In this in vitro study the direct interference of PHA isolectins with the cellular metabolism of differentiated Caco-2 cells can be investigated. To detect any differences in their effect upon the cellular metabolism, PHA-L4 and PHA-E4 were tested separately.…”
Section: Discussionmentioning
confidence: 99%
“…The Caco-2 cells were grown in Dulbecco's modified Eagle medium (DMEM) (Flow Laboratories, Amstelstad BV, Amsterdam, The Netherlands) supplemented with 1% (v/v) nonessential amino acids (Flow), 50 [ig of gentamicin/ml (Flow), 10 mM sodium bicarbonate (Flow), 25 mM Hepes (Flow), and 20% (v/v) fetal calf serum (FCS) (Sanbio BV, Uden, The Netherlands) and cultured at 37°C in a humidified atmosphere of 5% CO2 in air. The cells were seeded at 4.…”
Section: Caco-2 Cell Culturementioning
confidence: 99%